Ação comunicativa na organização do primeiro encontro de ex-alunos de licenciatura em física - Lopes, Nataly Carvalho [UNESP]; Carvalho, Lizete Maria Orquiza de [UNESP]; Carvalho, Washington Luiz Pacheco de [UNESP] (My University, 2011)
In this paper, we aim to understand the discourses of public school teachers who were former students of an Undergraduate Physics Education course, when they are perceived as actors speakers a public sphere concerned about teacher eduaction. So, we focused virtual dialogues occurred between these former students and a professor of the same course during the organization of the First Meeting of Ex-students inserted in an annual event called Meeting of the Teaching Practice in Physics of Ilha Solteira (ENPEFIS). Thus, we analyze these dialogues according to concepts of public sphere, communicative action and teachers as intellectuals according to elements of the content analysis of these virtual dialogues. Therefore, we envision in this work an important discussion for science teaching , since it reflects briefly on Physics Education committed to discussing science teaching in order to overcome the dogmatic and instrumental science education.

Neste trabalho, buscamos compreender os discursos de professores ex-alunos do curso de licenciatura em Física de uma universidade, quando eles são percebidos como atores falantes de uma esfera pública preocupada com a formação de professores. Por isso, analisamos os diálogos virtuais ocorridos entre estes ex-alunos e uma professora do mesmo curso para a organização o I Encontro de Ex-alunos inserido no evento anual do Encontro de Prática de Ensino da Física de Ilha Solteira (ENPEFIS). Assim, analisamos estes diálogos à luz dos conceitos de esfera pública, ação comunicativa, de professores como intelectuais e de acordo com os elementos da análise do conteúdo destes diálogos virtuais. Portanto, vislumbramos neste trabalho, uma discussão importante para o ensino de ciências, já que reflete rapidamente sobre a licenciatura em Física comprometida em discutir o ensino de ciências de forma a superar a educação dogmática e instrumentalizada das ciências.
Communicative action in the organization of the first meeting of ex-students degree in physics
Keywords: Communicative action; Public sphere; Formation of teachers; Former students; Sscience education; Ação comunicativa; Esfera pública; Formação de professores; Ex-alunos; Ensino de ciências